The Relationship between The Knowledge, Attitude, and Perceived Nursing Skill Based on Patient Safety of Professional Nurses in Police General Hospital - หัตถกี ปุณยารัตน์; แก้วสงค์ ปริญญา (Journal of The Royal Thai Army Nurses, 2019)
The purposes of this study were to 1) describe knowledge, attitude, and perceived nursing skill based on patient safety goals of professional nurses in Police General Hospital, and 2) examine the correlations among those three variables. Two-hundred and seventy-eight persons with professional nurses in Police General Hospital were recruited by stratified random sampling method. Study Instruments consisted of 1) the Personal Data Record Form, 2) the Patient Safety Knowledge Questionnaire which had the confidence at .71 (KR-20), 3) the Patient Safety Attitude Questionnaire, and 4) Perceived of Patient Safety Skill Questionnaire had the Cronbach’s alpha coefficient at .86 and .95 consequently. Descriptive statistics and Pearson Product Moment Correlation Coefficient analysis were used to analyse data. The results revealed that most of the samples’ knowledge level of patient safety was good (51.10%) and their attitude toward patient safety was at excellent level (46.40%). Perceived nursing skill based on patient safety was at excellent level (59.70%). There was a significant correlation between attitude and perceived nursing skill based on patient safety (r =.731, p < .001), but the knowledge was not significantly correlated to attitude and perceived nursing skill based on patient safety (r = .057 and .018, p > .05, respectively). The findings of this study suggest that the development of patients’ safety should be promoted in order to improve hospital’s quality.